Analisis Pelaksanaan Sistem Manajemen Dokumen Akreditasi (Sismadak) Di Rumah Sakit Dr. Sumantri Kota Pare-Pare - Jumriani Kamila Mallingkan; Fairus Prihatin Idris; Hasriwiani Habo (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Nearly 80% of the hospital manages documents manually, so that the search process is slow, and documents are often lost or scattered and damaged due to time constraints in checking all documents owned by the hospital and often the officers are transferred to other parts of the unit so that the submission of reports those handed over by other officers became constrained.Method:Qualitative with a Quasi-Qualitative approach by exploring in depth through observation, in-depth interviews, and documentation. The technique of determining informants was carried out by purposive sampling and there were 1 Sismadak program operator, 7 Sismadak admin staff so that researchers could only collect 8 informants Result: human resources (Man), there are still many Sismadak admin officers who don't understand and forget how to do it. operating a program that does not exist Budget (Money) so that the admin officer is lazy and does not focus on inputting the accreditation reporting data of the facilities (Material) is complete but the obstacles experienced by the network system officers are less stable. Data storage is carried out by the Sismadak admin officer which must be filled in into a daily quality indicator form then documented so that the reporting records will be stored automatically when the achievement of the reporting results is carried out during the implementation of the Sismadak program. Conclusion: several Sismada admin officers k there are still those who do not understand inputting hospital accreditation reporting data through the Sismadak program. It is better if the hospital routinely provides training and direction from the Sismadak admin officer to focus more on inputting hospital accreditation reports regularly.